Learning Continuity in Response to Climate Emergencies: Pakistan's 2022 floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Kaye, Tom; Perry, Freya (EdTech Hub, 2023)
Building on EdTech Hub's preliminary insights, this extended resource explores Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders in identifying scalable and feasible ways of using EdTech in response to Pakistan’s 2022 floods and improving learning responses in future climate emergencies. We identified these approaches by interviewing flood-affected parents and teachers, government education officers, development partners, local NGOs, and international experts in education in emergencies. We find that during the different phases of response to the emergency, communities’ needs and infrastructural realities keep changing. However, existing responses to support learning have not been able to address these needs at scale. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Educational Television: A Rapid Evidence Review - Watson, Joe; McIntyre, Nora (EdTech Hub, 2020)
This Rapid Evidence Review (RER) gives an overview of the recent literature concerning how the use of educational television might support children’s learning in low- and middle-income countries (LMICs). In this review, educational television is defined as television designed with research-based knowledge of how children use and understand television that systematically incorporates academic or social curricula into its content. In low-income contexts, educational television material could be delivered through videos played in schools that are supported by corresponding teacher guidance (e.g. the Mexican school-based T elesecundaria programme), or broadcast on public channels (e.g. the Tanzanian animation, Ubongo Kids). As such, certain educational television projects are capable of functioning even in circumstances where access to formal schooling facilities is restricted. This review therefore provides information that is particularly valuable in the context of the COVID-19 pandemic.
Keywords: L:English UXZJW5DR; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Afzal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence